Tetrabutylammonium Iodide Mediated Sulfenylation of Polysubstituted 1H-Pyrazol-5-amines with Arylsulfonyl Hydrazides - He, Jing; Wei, Yueting; Li, Xuezhen; Dai, Bin; Liu, Ping (Synthesis, 2021)
A TBAI-mediated sulfenylation of N,3-diaryl-1-arylsulfonyl-1H-pyrazol-5-amines with arylsulfonyl hydrazides has been established, and an expanded inventory of N,5-diaryl-4-(arylthio)-1H-pyrazol-3-amines was constructed through C–S bond formation and N–S bond breaking. Mechanistic investigations suggest thiosulfonate as a key intermediate in the sulfenylation, and the detosylation is promoted by the generated arylsulfinic acid. The method is characterized by simple operating conditions, broad substrate range as well as gram-scale reaction.
Keywords: sulfenylation; 1H-pyrazol-5-amine; metal-free; arylsulfonyl hydrazide; TBAI